ANALISIS ANGGARAN OPERASIONAL SEBAGAI ALAT PENGENDALIAN MANAJEMEN PADA PT. BANK SULSELBAR - Yuswari Nur (Lembaga Penelitian dan Publikasi Nobel Indonesia, 2018)
This study aims to (1) Analyze the difference between the operational budget and the realization of the Bank Sulselbar, (2) Evaluate the difference that occurred in the operational budget of PT. Bank Sulselbar. This research was conducted at Bank Sulselbar Makassar by using data of operational budget realization of PT. Bank Sulselbar period 2012 to 2016. Based on the results of this study deviation of operational budget 2012 to 2016 obtained the conclusion that the deviation of operational budget of Bank Sulselbar still within acceptable control limits.